Consumption Imputation Errors in Administrative Data. (17th August 2021) - Baker, Scott R; Kueng, Lorenz; Meyer, Steffen; Pagel, Michaela
Abstract: Many research papers in household finance utilize annual snapshots of household wealth from administrative data, such as tax registries, to calculate "imputed consumption." However, trading costs, unobserved intrayear trades, or unobserved security characteristics may cause measurement error. We document how such errors vary across groups of individuals by income, portfolio characteristics, and wealth and how they are correlated with individual income and balance sheets, asset prices, and the business cycle using transaction-level retail brokerage account data. We find that the economic significance of imputation error is small in many research settings, and we discuss robustness checks and econometric specifications to minimize the impact of imputation error in future research. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.